Text Complexity in Digital Language Learning: Analyzing the Readability and Lexical Density of Duolingo's Guidance Textbook - Azzahra, Sekar; Silaban, Jelly Prima Krisnawati; Sinar, Tengku Silvana (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This paper establishes the lexical density and readability levels of the Duolingo guidance textbook, with the view of establishing further the accessibility levels that the textbook has for use in language learning by users. Qualitative content analysis was conducted on 10 segments of the guidance text; lexical density was determined through content word proportions analyzed and readability by the Flesch Reading Ease formula. The results ranged between 47.6% and 56.1% for lexical density, while for nouns, just one word class, the most frequent class of words for all observed segments was 24.9-32.5%. Scores for readability ranged from 53.21 to 85.2. For example, "How to Test Your Best" sections obtained very high readability scores of 85.2, whereas sections more suited to the content, such as "Reading Texts", scored as low as 53.21. Further analysis then showed that there indeed was a strategic range in the section's complexity: the technical content was generally higher in lexical density and low in readability scores, while practical guidance sections maintained higher accessibility. Given this is the conclusion, recommendations go to Duolingo on adding extra scaffolding mechanisms for complex parts by developing supplemental material at different proficiencies, including adaptive learning whereby the complexity of the content would change based on performance. Also, periodic assessment of textual complexity across different versions guarantees that users are uniformly having their experience across the world. The current study added to the cognition of how digital language learning materials balance the issues of accessibility and educational effectiveness